Examination of the frequency of patients with pre-diagnosed allergic contact dermatitis attending dermatology outpatient clinics and evaluation of patch test results (Annals of Medical Research, 2021)
Aim: In this study, it is aimed to investigate the frequency of attending dermatology outpatient clinics and patch test results in the light of demographic characteristics of patients who underwent patch tests with a preliminary diagnosis of allergic contact dermatitis (ACD) in 2018-2019.Material and Methods: The files of patients who had a patch test with a preliminary diagnosis of allergic contact dermatitis were scanned retrospectively. Demographic characteristics such as age, gender, profession, number of attending to the dermatology outpatient clinic with the same complaint and the reactions determined as a result of the patch tests were examined.Results: A total of 122 patients with 67 (54.9%) male and 55 (45.1%) females were included in this study. The median duration of lesions was 24 (minimum 1, maximum 360) months. Fifty-eight (47.5%) patients had been attending the Dermatology outpatient clinic at least three times with the same complaint. Patients who attended to the dermatology outpatient clinics at least 3 times and had at least one positive patch test were including cobalt positivity as 29.3%, potassium dichromate as 27.5%, nickel as 24.1%, colophony as 13.8% and thiuram mix as 10.3%. There were 81 (66.4%) patients with at least one positive patch test results, 52 (42.6%) with at least two positives, and 33 (27%) with three positives. The three items that were at least one positive were nickel sulfate (26.2%), cobalt (25.4%), potassium dichromate (20.5%), respectively. Three items with three positivity were nickel (13.9%), potassium dichromate (4.1%), and mercaptobenzothiazole (2.5%), respectively. No positivity was found for benzocaine, 2-Methoxy-6-n-pentyl-4-benzoquinone, and clioquinol.Conclusion: In this study, the frequency of patients with ACD attending to the dermatology outpatient clinics at least 3 times was found approximately 50%. These results emphasize the importance of patch test awareness about the preventive medicine approach in our country. Also, the items causing ACD according to the degree of positivity were reported for the first time in this study. It was found that nickel and potassium dichromate, which are used relatively common in industries, are the most common strong allergens.
Keywords: Allergic contact dermatitis; allergens; patch test